Comparative Analysis Of Flexible Pavement Damage Models Between MDPJ 2024 And Asphalt Institute And AASHTO MEPDG - Pasaribu, Kevin Briant; Rahman, Taqia; Suparma, Latif Budi (Jurnal Multidisiplin Indonesia, 2025)
Reliable road infrastructure is crucial for the economy. However, high traffic loads can accelerate damage to flexible pavements, primarily fatigue cracking and permanent deformation (rutting). This study evaluates the performance of pavement structures designed according to the Indonesian Pavement Design Manual (MDPJ) 2024 by comparing its damage predictions against international methods, namely the Asphalt Institute and AASHTO MEPDG, across various road classifications. Through mechanistic simulation using KENPAVE, the resulting strain values were used as input to predict the number of allowable load repetitions (ESAL) until failure occurs. The results show that all three methods consistently identify fatigue cracking as the critical damage type that occurs before rutting. However, there are significant differences in the magnitude of the predicted ESAL values. The Asphalt Institute method is the most conservative, producing the lowest fatigue cracking ESAL, while AASHTO MEPDG predictions are closer to, yet still lower than, the most optimistic predictions of MDPJ 2024. Therefore, this study concludes that further calibration of the MDPJ 2024 model with actual field data is essential to improve the accuracy of service life predictions for pavements in Indonesia.